Semiotic Analysis of Characteristic Image of Jogja Society in the film of “Jagad X-Code” - Herawati - (The Indonesian Journal of Communication Studies, 2010)
The object of the research is the film of Jagad X-Code. The film of Jagad X-Code took DI Yogyakarta as the setting of this film. The people of Jogja maintain the strong characteristic of Java which is represented in this comedy film. It conveyed the cultural values which started to fade away. The aim of the research is to identify the symbols and the sign used and the characteristic of the Jogja people presented in the film ‘Jagad X-Code’, and to identify the meaning of the film. The data source helped the writer in the process of interpretation and significance of the film was obtained through observation to the film, information from the book, internet and informants who understood the javanese culture. It is concluded that film is one of media which convey the cultural value which should be maintained by the society. The characteristics of Javanese People represented in this film are submissive, polite, respectful to the elderly, helpful, and innocent. These characteristics are symbolized by the director of the film through the attitude and behavior of the actor in the film.